The Impact of Internet Access on Unemployment Rate in Pandemic Crisis Management (COVID-19 Case) - Mozhgan Moallemi; Mahdi Fadaee Khorasgani (فرایند مدیریت و توسعه, 2023)
Purpose: This study intended to compare the effects of internet access on unemployment rates in the two time periods before and after COVID-19. Methodology: The research method was causal-disability-analysis. By estimating two regression models and using panel data method for the period of the coronavirus pandemic and the years before it, the impact of internet accessibility index on unemployment rate in these two periods in EU and MENA countries was estimated. Findings: A 10 percent increase in internet access during the COVID-19 pandemic has led to a 0.1 percent decline and in the period before the coronavirus it only led to a 0.04 percent decrease in the unemployment rate. Originality: The contribution of the current study is investigating the impact of internet access on unemployment rate in terms of providing remote working conditions in public quarantines caused by the coronavirus epidemic. Implications: To better manage any future pandemic crisis, policy makers in the field of information and communication technology need to consider the importance of the impact of internet access on the unemployment rate. To realize this, we have suggested the following administrative approaches: internet accessibility, managing the process of supporting enterprises, strengthening export capacity, and expanding e-government services.